Biofilms by bacterial human pathogens:Clinical relevance - development, composition and regulation - therapeutical strategies - Adina Schulze; Fabian Mitterer; Joao P. Pombo; Stefan Schild (Microbial Cell)
Notably, bacterial biofilm formation is increasingly recog-nized as a passive virulence factor facilitating many infec-tious disease processes. In this review we will focus on bacterial biofilms formed by human pathogens and high-light their relevance for diverse diseases. Along biofilm composition and regulation emphasis is laid on the inten-sively studied biofilms of Vibrio cholerae, Pseudomonas aeruginosa and Staphylococcus spp., which are commonly used as biofilm model organisms and therefore contribute to our general understanding of bacterial biofilm (patho-)physiology. Finally, therapeutical intervention strategies targeting biofilms will be discussed.